Psychological Well-Being and Organizational Commitment with Turnover Intention Among Generation Z Employees - Al Farabi, Iltizam; Matulessy, Andik; Rini, Amanda Pasca (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to examine the relationship between psychological well-being and organizational commitment with turnover intention among Generation Z employees. Generation Z refers to individuals born between 1995 and 2010, characterized by unique traits in the workplace, including a high tendency for turnover intention. This research employs a correlational quantitative approach involving 350 Generation Z employees as participants. Data were collected using three scales: the psychological well-being scale, organizational commitment scale, and turnover intention scale. The results indicate a significant relationship between psychological well-being and organizational commitment with turnover intention (R = 0.839, p < 0.01), with an effective contribution of 70.4%. Partially, psychological well-being has a significant negative relationship with turnover intention (t = -3.606, p < 0.05), as does organizational commitment (t = -5.079, p < 0.05). This finding demonstrates that higher levels of psychological well-being and organizational commitment are associated with lower turnover intention among employees. These results provide important contributions to human resource management, particularly in fostering the well-being and commitment of Generation Z employees to reduce turnover intention levels.